155k views
4 votes
Simplify the difference. (–7x – 5x^4 + 5) – (–7x^4 – 5 – 9x)

User VanTanev
by
4.8k points

1 Answer

3 votes

Answer:
2x^4+2x+10

Explanation:

You need to remember the mulplication of signs:


(+)(+)=+\\(-)(-)=+\\(-)(+)=-

Knowing this, you can distributive the negative sign. Then you get:


(-7x- 5x^4 + 5) - (-7x^4 - 5 - 9x)=-7x- 5x^4 + 5 +7x^4 + 5 + 9x

Now you need to add the like terms. Then:


=2x+2x^4+10

Finally, you can order the polynomial obtained in descending order. Therefore, the answer is:


=2x^4+2x+10

User Toddwseattle
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.